Answers

2016-03-19T20:56:54+08:00
Let  x =  numerator   & y  = denominator
     thus   x + y   = 22     /   x =   22-y
   
      also      x + 5   =     14/11
                   y -  2   
       substituting  for    x
           22-y +5   =     14
            y -2                11

      thus    11(27-y)   =  14 (y-2)         /  cross multiplication  
                  297-11 y   =  14 y -28
                       25 y =    325
                             y = 13
                   x+y =  22
                   x+13 = 22
                    x =  9
   therefore the original equation is       9/13


0